The Development of Educational Institutions Under Government Management in Classic and Modern Ages - Nasrullah, Nasrullah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This study aims to determine the beginning of the emergence of formal institutions in classical times and to determine the development of the state archives office in classical and modern times and to determine the development of Al-Shalunat al-Adabiyah in classical and modern times. This study uses a literature review approach. Literature Review is the result of analyzing various conceptual information as well as qualitative and quantitative data from various previously published scientific articles. The method used in this research is literature study which functions as a guide in studying a research problem (review of research). Based on the results of the analysis of this research, it is known that the appearance of the institution mentioned by Goerge Makdisi is a government institution as part of an educational institution, namely the negata archives office (a school for prospective government secretaries). The state archives office is a school for secretaries of all levels who work in government. School is the main place of education for prospective secretaries who are the backbone of humanities studies. If it is described with an existing institution, this state archives office is the same as the IPDN Institution (Internal Administration Institution). The next educational institution is a literary studio or As-Shalunat al-Adabiyah which can be interpreted as a place to perform reading and study literature, or as a cultural or theater center, such as the Ismail Marzuki Park in Jakarta. In carrying out the activities of the literary assembly, each Khalifah has certain clues.